High Performance of Power Cables Using Nanocomposites Insulation Materials - Mohamed Fouad; Ahmed Thabet; Abdel-Moamen Ahmed; Ahmed Elnodi (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2021)
Partial discharges occur the biggest failure problem in power cable insulation due to distortion of electrical stress. In this paper, it has been investigated on the effect of spherical nanoparticles of Barium titanate (BaTiO3) and Clay for enhancing electrostatic field distribution in single and three-core power cables. It has been applied new strategies of nanotechnology techniques for designing innovative polyvinyl chloride insulation materials by using nanocomposites and multi-nanocomposites. Moreover, it has been studied the electrostatic field distribution within power cable nanocomposites insulation in presence of air voids, water voids and cupper impurity voids. The electrostatic field distribution in power cable insulation has been calculated by finite element method (FEM). A comparative study has been investigated on the effect of nanocomposite insulation for enhancing electric field stress in power cables.